2013
DOI: 10.1152/jn.00481.2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative examination of stimulus-response relations in cortical networks in vitro

Abstract: Variable responses of neuronal networks to repeated sensory or electrical stimuli reflect the interaction of the stimulus' response with ongoing activity in the brain and its modulation by adaptive mechanisms, such as cognitive context, network state, or cellular excitability and synaptic transmission capability. Here, we focus on reliability, length, delays, and variability of evoked responses with respect to their spatial distribution, interaction with spontaneous activity in the networks, and the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 55 publications
(68 reference statements)
3
49
0
Order By: Relevance
“…Hence, they might interfere with our capacity to interpret the impacts of stimulation on response dynamics (Wallach and Marom, 2012; Weihberger et al, 2013). Network spikes may be suppressed by pharmacological blockage of NMDA channels in cultured cortical networks (Robinson et al, 1993; Jimbo et al, 2000; Bonzano et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, they might interfere with our capacity to interpret the impacts of stimulation on response dynamics (Wallach and Marom, 2012; Weihberger et al, 2013). Network spikes may be suppressed by pharmacological blockage of NMDA channels in cultured cortical networks (Robinson et al, 1993; Jimbo et al, 2000; Bonzano et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…This preparation proved useful, over the past 10–15 years, as a toy model in the study of functional network processes, ranging from development and adaptation to learning and stimulus representation (Maeda et al, 1995; Kamioka et al, 1996; Jimbo et al, 1998, 1999; Tateno and Jimbo, 1999; Shahaf and Marom, 2001; Corner et al, 2002; Eytan et al, 2003; Shahaf et al, 2008). A recent series of studies demonstrated the efficacy of several closed loop applications in controlling aspects of activity in these in vitro large-scale cortical networks (e.g., Wagenaar and Potter, 2004; Wagenaar et al, 2005; Arsiero et al, 2007; Rolston et al, 2010; Wallach et al, 2011; Weihberger et al, 2013). Here we implement one of these approaches, the so-called “response-clamp” procedure: a PI (Proportional-Integral) negative feedback algorithm (Wallach et al, 2011; Wallach, 2013), in order to control response features in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…1 or ∞). Based on previous results reported in the literature for regular stimulation [49, 50], we chose 0.2 Hz as a separation frequency in order to distinguish between two different conditions: time-dependence (MSR > 0.2 Hz) or independence (MSR < 0.2 Hz) of responses to subsequent stimuli. It is possible to note how the network preference for irregular stimulation sequences described above holds true only for fast sequences (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, a paper published by the group of Egert [50] suggested that strength and duration of neural network responses to electrical stimulations followed an exponential saturating profile as a function of the length of the preceding inactivity period. These results were compatible with short-term synaptic depression caused by bursts, due to depletion of readily releasable pool of neurotransmitter vesicles, also in conjunction with GABAergic inhibition (see Discussion of [50]).…”
Section: Discussionmentioning
confidence: 99%